Efficacy of Epley’s Maneuver in Benign Paroxysmal Positional Vertigo (BPPV) - Sainch, Sana; Asghar, Adnan; Siddiqui, Fatima; Maqbool, Shahzad; Aslam, Sohail; Saleem, Kiran (Biological and Clinical Sciences Research Journal, 2025)
Vertigo is among the most common complaints in patients visiting ENT outpatient departments (OPD), especially among the elderly, where it significantly increases the risk of falls. One of the leading causes of neurological vertigo is Benign Paroxysmal Positional Vertigo (BPPV), a vestibular disorder that, although self-limiting, can cause recurrent episodes and impair quality of life, particularly with advancing age. Epley’s maneuver is a noninvasive, cost-effective repositioning technique designed to treat posterior canal BPPV by relocating canaliths from the semicircular canal to the utricle. Objective: To evaluate the effectiveness of Epley’s maneuver in patients diagnosed with posterior canal BPPV. Methods: This prospective observational study was conducted at the ENT Outpatient Department of PNS SHIFA Hospital, Karachi from January 2023 to December 2023. A total of 90 patients diagnosed with posterior canal BPPV were enrolled using non-probability convenience sampling, with the sample size based on previous studies. Participants were randomized into three equal groups (n=30): Group A received only medical therapy, Group B underwent Epley’s maneuver alone, and Group C received both Epley’s maneuver and medical treatment. Follow-up assessments were conducted at the 2nd and 4th weeks to evaluate symptom resolution and improvement in quality of life. Statistical analysis was performed using SPSS v25. Chi-square and ANOVA tests were applied, with a p-value <0.05 considered significant. Results: Patients treated with Epley’s maneuver (Groups B and C) showed significantly greater symptomatic relief at both the 2nd and 4th-week follow-ups compared to those receiving only medical management (Group A). The combination of Epley’s maneuver with medication (Group C) yielded the highest rates of symptom resolution. Quality-of-life scores and functional assessments showed marked improvement in the maneuver groups compared to the medicine-only group (p<0.05). Conclusion: Epley’s maneuver is an effective, non-invasive intervention for managing posterior canal BPPV. When combined with medical therapy, it enhances treatment outcomes and significantly improves patient quality of life compared to medical management alone.